FENOMENA ISTRI BEKERJA PERSPEKTIF HUKUM ISLAM (Studi Kasus di Kabupaten Temanggung) - Desi Anggraeni; M. Ali Mubarok (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Wives are often the economic contributors of families, especially those with low income. They are additional income earners for the family. This phenomenon also occurs in Temanggung Regency. They work in various sectors, from the domestic to the public sector, because most men in Temanggung work as farmers and laborers, so their income does not fulfill the family's economic needs. This article examines the phenomenon of working wives in Temanggung Regency from the perspective of Islamic law and Talcott Parson's structural-functionalism theory. In the Qur'an, the husband's responsibility is to complete the family's needs according to his portion of the duties because men have physical advantages over women. Islamic law allows wives to work in Temanggung if they do not neglect their primary duties as homemakers. However, Islam is not permitted if it will cause disharmony in the family. From Parson's perspective, it has been classified that the wife's job is to work at home, and the husband's job is to work outside, so there is no competition in the household. Regardless, working wives in Temanggung help husbands fulfill family needs to overcome dysfunctional household harmony